REHABILITATION OF PATIENTS AFTER CLOSED OSTEOSYNTHESIS DIAPHYSARY FRACTURES OF THE SHINK BONE - Kovalchuk P. Ye.; Tsyrkot І. M.; Tulyulyuk S. V. (World Science, 2021)
Bone damage in fractures is never isolated and is always accompanied by soft tissue damage, microcirculation and neurotrophic processes. The severity of these disorders depends on a number of factors: the mechanism of injury, type and location of the fracture, the magnitude of the displacement of the fragments, the size of the hematoma in the fracture area. One analyzed the rehabilitation treatment after closed osteosynthesis of the tibia in 53 patients with fractures and their consequences (nonhealing fractures, pseudoarthrosis) that were operated with the use of blocking intramedullary metal polymeric fixation devices BIMPF – 3M and BIMPF – 8. No infectious complication was noted, one patient was characterized by a delayed consolidation of fragments in case of closed BIMPO. The average terms of fragments consolidation with a complete restoration of an operated extremity ranged from 10 to 12 weeks in case of dynamic version of BIMPO and 13 – 15 weeks with a static one.